Estrategias de difusión para el reconocimiento del Centro de Innovación Tecnológica para Calzado (CITCA) en la provincia de Tungurahua - Tubón Tamayo, Génesis Mishelle (2024)
The specific aspects of the footwear sector that have brought about changes in the present Integrative Project are analyzed. The causes that have influenced the footwear industry in the province of Tungurahua have been investigated. Through the shared experience of experts and individuals immersed in this field, and by means of a quantitative approach, the impact of leather and footwear production on the country has been understood. The main objective of this project is to give recognition to the Center for Technological Innovation in Footwear (CITCA) within the market through proposed diffusion strategies for subsequent execution. The strategies are outlined and specified within a digital manual. The results lead to the conclusion of the necessity to integrate a digital campaign and propose a brand activation to enhance the visibility of this Technological Innovation Center within its target audience, thus aiding in the improvement of the footwear sector's development within the province. In summary, the integrative project analyzes specific aspects of the footwear sector, investigates causes that have positively and negatively influenced the industry in the province of Tungurahua, and seeks to recognize CITCA in the market through diffusion strategies. With these actions, it is expected to improve the sector's development and foster collaboration between footwear companies, enhancing the quality of the Ecuadorian product.